SDRIFE: symmetric intertriginous flexural exanthema related to ciprofloxacin and/or nitrofurantoin administration: a case report - Rodríguez-Suárez, María D. L. C.; Ortuz-Lessa, Camila; Amador Eleuterio, Sarahi; Gallegos-Ramos, Arely Lisette; Sanabria-Deseuza, Jose Antonio (International Journal of Research in Medical Sciences, 2025)
Symmetrical drug-related intertriginous and flexural exanthema (SDRIFE) is a self-limited cutaneous reaction induced by systemic drug exposure. It typically presents as sharply demarcated, symmetrical erythematous lesions affecting intertriginous areas such as the gluteal, perianal, and inguinal/perigenital regions, without systemic symptoms. Despite established diagnostic criteria, SDRIFE remains rarely reported, most often associated with antibiotics and less commonly with antifungals. We report the case of a 76-year-old woman with type 2 diabetes who developed SDRIFE after receiving ciprofloxacin and nitrofurantoin for a urinary tract infection. Treatment with corticosteroids led to marked clinical improvement. This case is of particular interest, as only one previous report has linked SDRIFE to ciprofloxacin, and none to nitrofurantoin. SDRIFE is believed to represent a type IV hypersensitivity reaction, most commonly triggered by beta-lactam antibiotics, though non-beta-lactams may also play a role. The clear temporal association between drug administration and symptom onset in our patient suggests a likely causal relationship. Given the limited documentation of SDRIFE associated with these agents, this case highlights the need to consider a broader range of potential drug triggers in patients presenting with this distinctive eruption.